PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. AGUNG AUTOMALL CABANG DURI - Novia Novia; Marzolina Marzolina; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research conducted at PT. Agung Automall Branch of Duri with the purpose to determine and analyze the influence of work environment and work stress by simultant and partial on employee morale at PT. Agung Automall Branch of Duri. Population and sample in this research it is a 60 employee of all employee the operational part in PT. Agung Automall Branch of Duri. Data collection methods used through questionnaires, interviews and documentation. Data analysis used is descriptive, as it also used quantitative analysis, specifically using multiple linear regression with the help of the SPSS program version 18.0. Of the research and data processing has been done. Simultan regression test (F Test) show the work environment and work stress has a significant effect on employee morale at PT. Agung Automall Branch of Duri. The result of partial test (t Test) show that work environment partially has a significant impact on employee morale at PT. Agung Automall Branch of Duri. Of the research conducted it is suggested to the company to pay more attention the work environment and work stress of employees, especially employee of part servce and sales so that make employees more passion in their work so that the work of employees in company even become more optimal.Keywords : work environment, work stres and morale